Racetrack logic. Issue 22 (1st October 2017) - Vacca, M.; Graziano, M.; Ottavi, M
Abstract : A building block for computing in memory systems is introduced. Based on the previously introduced racetrack memory proposed by IBM, a racetrack memory is used not only to store data but also to perform bitwise majority‐based computations by coupling the memory with inputs provided by controllable magnets. This solution is defined as racetrack logic. Micromagnetic simulations are used to confirm that the proposed solution is technically viable.